The Effect Of Profitability, Liquidity And Capital Structure On Company Value With Gcg As A Moderating Variable In The Fnb Sector - Melly Engely; Hadi Santoso (Al-Kharaj: Journal of Islamic Economic and Business, 2026)
This study examines the influence of profitability, liquidity, and capital structure, with GCG as a moderating variable. The focus of this study is on food and beverage companies listed on the Indonesia Stock Exchange (IDX) between 2020 and 2024. This study uses a quantitative method based on panel data with the Eviews 13 tool. Profitability is measured using Return on Assets (ROA), liquidity using the Current Ratio (CR), capital structure using the Debt to Earnings Ratio (DER), and firm value using Price to Book Value (PBV), and GCG using Independent Commissioners (KI). The test results reveal that profitability and capital structure have a positive impact on increasing firm value, while liquidity tends to decrease it. Interestingly, the use of GCG moderates the relationship between liquidity and firm value. However, GCG does not moderate the relationship between profitability and firm value or the relationship between capital structure and firm value.